2014
DOI: 10.5121/ijnsa.2014.6106
|View full text |Cite
|
Sign up to set email alerts
|

A Fair Exchange & Customer Anonymity Protocol Using A Trusted Third Party for Electronic Commerce Transactions & Payments

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The integrated literature review suggests that fair exchange positively leads to a high level of trust in P2P platform transactions (Alqahtani 2014). For example, McKnight et al (2002) demonstrated that fairness (i.e., structural assurance) enables online users to enhance the degree of trusting beliefs.…”
Section: H4 Market Opportunity Of P2p Platform Positively Influences Trusting Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrated literature review suggests that fair exchange positively leads to a high level of trust in P2P platform transactions (Alqahtani 2014). For example, McKnight et al (2002) demonstrated that fairness (i.e., structural assurance) enables online users to enhance the degree of trusting beliefs.…”
Section: H4 Market Opportunity Of P2p Platform Positively Influences Trusting Beliefsmentioning
confidence: 99%
“…Finally, fairness can be defined as the basic premise of justice experienced from online platforms, and is a significant component for facilitating the psychological relationship between consumers and providers in the sharing economy (Ryu et al 2014). Alqahtani (2014) addressed the characteristic of fairness, offering optimistic fair exchange for online users in trust management, which can be supported by the theoretical views of resource exchange theory underlying the importance of social justice and change as a process of fair exchanges between parties (Brinberg and Wood 1983). Similarly, (individuals may pursue trusted interactions with others without any internal and/or external constraints in an online context (Medina et al 2015).…”
Section: Introductionmentioning
confidence: 99%